Optimization of Hydraulic Characteristics in Inlet Area of Fishway at High Flow Rate - ZHANG Jun; ZHANG Zhiguang; KANG Xiangwen; LI Wenyi; ZHENG Tiegang (Renmin Zhujiang)
The hydraulic characteristics in the inlet area of the fishway are directly related to the effect of attracting fish at the inlet, and it is the key to ensuring the operation effect of the fishway. In order to improve the poor effect of attracting fish at the inlet of the fishway, this paper presented an optimization device for hydraulic characteristics in the inlet area of the fishway at a high flow rate and established a three-dimensional hydrodynamic model. The paper also studied the improvement effect of different optimization schemes on the flow conditions for attracting fish at the inlet of the fishway. The results show that adding a rectifier building downstream at the inlet of the fishway can effectively improve the flow characteristics in the inlet area at a high flow rate. According to the comparative study of the body shape, the recommended body shape of the rectifier building is as follows: a diversion pier angle of 20°, oblique guide wall angle of 36°, inlet width of 5 m, outlet width of 5 m, direct guide wall length of 10 m, and spur dike length of 10 m. Based on the recommended scheme, the inlet area of the fishway can form a continuous and effective fishway at a high flow rate. The research results can provide a reference for the design and regulation of the inlet area of the fishway.